Chemometrics reveals oil sources in the Fangzheng Fault Depression, NE China. (December 2016) - Wang, Yao-Ping; Zhang, Fan; Zou, Yan-Rong; Zhan, Zhao-Wen; Peng, Ping'an
Highlights: A total of 125 source rock and oil samples were collected and analyzed using GC–MS. PCA and multidimensional scaling were used for oil–source rock correlation. Crude oils are mainly generated from the Xinancun-Wuyun Formation. Abstract: One hundred and twenty-five rock and oil samples collected from the Fangzheng Fault Depression were analyzed by GC–MS. Principal component analysis (PCA) and multidimensional scaling (MDS) based on nine biomarker ratios were used for oil–source rock correlation in this region. The oils are characterized by a predominance of low to middle molecular weight normal alkanes ( n -C12 – n -C20 or n -C12 – n -C25 ), moderate to high Pr/Ph ratios (1.44–5.3), relatively low C27 /C29 regular steranes, C35 /C34 hopanes and gammacerane/C31 R ratios, all of which suggest relatively oxic conditions under fresh water depositional conditions with significant terrigenous organic matter input. PCA and MDS results show that the investigated oils were derived mainly from the Xinancun-Wuyun Formation and also illustrate the maturation and depositional conditions of the rocks and oils through an MDS plot. We show that MDS is a reliable, multi-parameter oil–source rock correlation method.